El aprendizaje de la lengua latina para la composición literaria: noticias de la preceptiva estilística medieval y neolatina. - Sánchez Manzano, Mª Asunción (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
The scholars, who followed Norden often express their reluctance in view of unexpected composition features in medieval Latin, so as the neolatin literary production. The reader could find a report on the valuable norm, which pretended to be useful for Latin texts composition. The claim for language correction is the main concept required, but it is followed by some traditional requirements, and on the other hand, the peculiar kind of excellence, that is selected each time according to cultural movements. The sign of a literary text is the difference from colloquial language. The tradition of «schemata» enclose comparative literature studies and language philosophy, and in advance, any special language selection, as a sign of literary form, is not required. Our purpose is the analysis of the elements, we know by medieval and renaissance companions, which conditioned literary texts composition.